THE INFLUENCE OF WORK CLIMATE ON NURSE PERFORMANCE IN THE INPATIENT INSTALLATION OF MALAHAYATI ISLAMIC HOSPITAL IN MEDAN: WORK CLIMATE ON NURSE PERFORMANCE - harahap, Preti Sinta; Agustina, Dewi; Harahap, Rezki Safitri; Fadila, Naswa; Wulandari, Nadiah; Nazhifah, Nasywa; Majid, Restu Amalia (STIKes Mandala Waluya Kendari, 2024)
Background: This study aims to analyze the influence of work climate on nurse performance in the Inpatient Installation of Malahayati Islamic Hospital, Medan. Nurses at this hospital have reported dissatisfaction with compensation and recognition systems, which are thought to affect performance. Methods: A quantitative approach was employed, using purposive sampling to survey 49 nurses. Data were collected between September 23 and October 5, 2024, through questionnaires, focusing on work attitudes, salary, incentives, and reward provision. Chi-Square analysis was applied to evaluate the relationships between these variables and nurse performance Results: The findings revealed that a positive work attitude is significantly associated with improved performance. Low salary showed a negative effect, with an Odds Ratio (OR) of 0.563 and a p-value of 0.004. Incentives positively influenced performance (OR = 0.263, p-value = 0.000), while reward provision indicated a trend towards significance (OR = 8.667, p-value = 0.056). Conclusion: This study concludes that enhancing salary, incentives, and recognition systems is essential to improving nurse performance.